Per una pedagogia della pace - Andrea Cecconi (Studi sulla Formazione)
The article addresses Ernesto Balducci’s point of view for the construction of a pedagogy of peace: in a context marked by globalization, which proposes a global model of modernity and a uniform pattern of behaviors and values, Balducci’s contribution to promoting an education that tends to overcome an ethnocentric and Eurocentric viewpoint and legitimizes a planetary viewpoint, capable of integrating in itself also the gaze and hopes of the other.